Outcome of Infant Extracerebral Fluid Collections - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Cases of benign infantile extracerebral fluid collections and nontraumatic chronic subdural hygroma or hematoma were reviewed retrospectively at Nebraska Medical Center, Omaha.